THE EFFECT OF ACADEMIC SUPERVISION AND PRINCIPAL'S LEADERSHIP ON TEACHER PERFORMANCE THROUGH WORK MOTIVATION IN SD NEGERI TAASIFETO BARAT BELU DISTRICT, EAST NUSA TENGGARA - Santos, Richardus Dos; Rusdarti, Rusdarti; Edy Mulyono, Sungkowo (Educational Management, 2020)
This study is aimed at examining the effect of academic supervision and leadership of the principal on teacher performance mediated by teacher work motivation. The method used in this study is a quantitative method, the results of the study will be processed using some statistical analysis, namely by using descriptive analysis techniques and path analysis techniques with the help of the SPSS program. The number of respondents used in this study was 75 respondents. All respondents were all public elementary school (SDN) teachers in the Tasifeto Barat-Belu-NTT Sub district which were spread across twelve Public Elementary Schools. Based on the results of the path analysis, it was concluded that academic supervision and leadership of the school principal either partially or simultaneously had a significant effect on work motivation and teacher performance, Furthermore, the analysis also showed that work motivation also has a significant effect on teacher performance, this showed that the better the academic supervision and leadership of the principal, the higher the teacher's work motivation can further improve teacher performance.